The Effect of Implementing Occupational Safety and Health Programs on Employee Productivity at PT. Consolidated Electric (CEPA) Power Asia Wajo District - Muhammad, Karlyna Bte; Thamrin, Yahya; A, Arman (PT.Mantaya Idea Batara, 2021)
Occupational health and safety programs have been implemented by many organizations which it is aimed to reduce or avoid risk of work accidents. The occupational health and safety management system is a systematic and comprehensive occupational health and safety management concept in a complete management system. Through the process of planning, implementing, measuring, and monitoring. This research was a quantitative research with analytical observational method through a Cross Sectional Study approach. The data was analyzed by Chi- Square test and Logistic Regression test. The sampling technique used in this study was total sampling with 40 employees as samples. The results of the study using the Chi-Square test for the P-Value measurement and monitoring variable of 0.001, the P-Value Accident Prevention variable of 0.000, the P-Value Disease Prevention variable of 0.000, the P-Value stress management variable of 0.525 and the Health Program variable. P-Value is 0.001. The conclusion in this study is based on the P-Value < 0.05, there is a relationship between the variables of measurement and supervision, accident prevention, disease prevention, and health programs on employee productivity at PT. CEPA Wajo Regency and there is no relationship between stress management variables on work productivity of employees at PT. CEPA Wajo Regency. Based on the value of Exp (B) / Odds Ratio in the multivariate analysis test using the Logistics Regression test, the accident prevention variable is the most influential factor on employee productivity at PT. CEPA, Wajo Regency with a value of 16,460. The suggestion in this research is to put more emphasis on the implementation of the OHS program by making company policies on OHS, so that all employees have a deeper awareness and knowledge of the OHS program so that they can implement the OHS program better